THE INFLUENCE OF ARABIC IN THE ISLAMIC WORLD AND FUTURE TECHNOLOGICAL DEVELOPMENTS - Rahmatia Safitri; Rita Zahara Kamsir; Meisil Yanda (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Arabic has a significant role in the Islamic world and has a great influence on various aspects of Muslim life. Along with the development of technology, the influence of Arabic has also developed and plays an important role in the future of technology. This study aims to explore the influence of Arabic in the Islamic world and analyze how this influence can affect the development of technology in the future. This study uses a literature study approach by analyzing secondary data from related references, such as scientific journals, books, and related articles. The results of the study show that Arabic has a major impact on the understanding of Islamic literature, as well as playing a role in the development of information and communication technology in the modern world. The influence of Arabic in the future is expected to increase along with globalization and rapid technological developments. From this study, it can be concluded that Arabic has an important role in the Islamic world and is a driver for innovation and technological development in the future. Learning Arabic is not only important for understanding the heritage of Islamic culture but also for responding to challenges and opportunities in the ever-evolving world of technology.